Subjects in the Paintings by J. A. Atkinson - Kustova, Anna E. (Actual Problems of Theory and History of Art, 2025)
The report is dedicated to the Russian subjects in the paintings by John Augustus Atkinson. In 1784–1801 he worked in St. Petersburg. Atkinson worked in Russia during the period of transition from Neoclassicism to Romanticism. It can be clearly seen in his canvases. In his work he combined English and Russian cultural traditions, which is a special feature of his individual manner. His painting gives us a good possibility to look at Russia from the foreign artist’s viewpoint .